Does the social status of the elderly impact morbidities among them? – A cross sectional Study in a district of Gujarat - Nagar, Shashwat S; Nagar, Noopur S; Patel, Hirenkumar B; Mahyavanshi, Darshan; Nagar, S S (Indian Journal of Community Health, 2021)
Background: The aging population is both medical & sociological problem for the country and they suffer with high rates of morbidity and mortality. So Social factors lay a significant impact on the health practices and this study will help us to understand and evaluate their health problems of elderly. Aims and Objective: 1. To assess the social status of elderly population. 2. To associate the findings with morbidities of elderly Methods: A cross sectional study was carried out in urban and rural area of Surendranagar district among 611 elderly, using a predesigned and pre tested questionnaire by directly questioning the subjects with oral and written consent. For selection of the area, in both areas, the sampling units were enumerated and samples were collected by using simple random sampling, data was entered and analyzed using MS excel 2007. Result: Nearly 60 % of the subjects were currently unemployed and the predominant family system was 3 generation family. Majority of the families in the urban areas were from social class 4, whereas in the rural areas were from social class 5. Having poor social score had a statistically significant association with presence of morbidity in elderly both areas. Conclusions: Majority of elderly in both urban and rural areas had a poor social status. Role of the family and social structure on the health of the elderly can be clearly established. However, support structure must be developed in our social system in a way that the destitute and dependent elderly are taken care of by either government system or social organizations like NGOs and old age home.